Analysis of 550 cases of thyroid nodule - Botta, Fernando; Delgado, Bolívar (Cirugía del Uruguay, 1996)
The authors select 550 cases with preoperative diagnosis of solitary or dominant thyroid nodu/e out of a review of c/inical folders of patients who had undergone surgery for thyroid patho/ogy The aim of this study is to show the usefulness of imagenological studies and cytology in the diagnostic evaluation of thyroid nodu/es. Out of the 550 cases, 51 O had undergone sean and 269 ultrasonography 75% of the nodu/es (327) appeared as co/d in the sean and 58% (156) were so/id in the US. Most of these were benign (87%). Although 79% of the carcinomas appeared as cold and 68% as so/id, 73% of the benign nodu/es were cold in the sean and 56% were so/id in the US. This shows high sensitivity of these studies, greater than 90%, but a very low specificity lower than 14%, and thus very low capacity far surgery selection.